Turnover Intention Analysis: the Effect of Job Stress, Job Insecurity, and Burnout as Intervening Variables in Medical Equipment Companies - Amri, Fahrizal; Harini, Sri; Yuningsih, Erni (PT FORMOSA CENDEKIA GLOBAL, 2023)
Turnover Intention is a problem that can be experienced by companies. High turnover intention can cause companies to experience Labor Turnover (LTO) problems, namely the rate of employee turnover. A high LTO level can disrupt company activities because the company requires more time and costs to find replacements for employees who leave, select prospective employees, and provide orientation to new employees. The aim of this research is to find out the direct influence of job stress, job insecurity and burnout on turnover intention and the indirect influence of job stress and job insecurity on turnover intention through burnout as an intervening variable. This research used a saturated sample method, namely 66 respondents who were employees of Medical Equipment Companies. Data processing uses path analysis with SPSS V 25. Based on path analysis, job stress, job insecurity, and burnout have a direct effect on turnover intention and then job stress has no effect on turnover intention through burnout and job insecurity has an indirect effect on turnover intention through burnout